Analisis Kemampuan Keuangan Daerah Pada Daerah Tertinggal di Provinsi Sulawesi Tengah - Rycha Kuwara Sari; Choiroel Woestho; Milda Handayani (Jurnal Kajian Ilmiah, 2021)
The regional capacity in managing the budget as reflected in the Regional Revenue and Expenditure Budget (APBD) means describing how the region's ability to finance any development activity by applying the principle of equity and justice by using regional potential. The research methodology used is descriptive research method. This method was chosen by the researcher in order to obtain an overview of various actual information in detail which is described in the aspect of regional financial capacity as measured by PAD share, PAD growth and PAD elasticity which are then combined into the regional financial capacity index method. The data selected is panel data in the form of the Regional Revenue and Expenditure Budget from 9 Districts / Cities that are categorized as disadvantaged areas during the 2015-2019 period which were obtained from the Directorate General of Fiscal Balance, Ministry of Finance. The results obtained are 6 districts that are classified as high regional financial capacity, 2 districts are classified as medium and 1 district are classified as low. Keywords: Disadvantaged Regions, PAD Growth, PAD Elasticity, Regional Financial Capability Index, Share of PAD, Abstrak Kemampuan daerah dalam mengelola anggaran yang tercermin dalam Anggaran Pendapatan dan Belanja Daerah (APBD) berarti menggambarkan bagaimana kemampuan daerah dalam membiayai setiap kegiatan pembangunan dengan menerapkan prinsip pemerataan dan berkeadilan dengan menggunakan potensi daerah. Metodologi penelitian yang digunakan adalah metode penelitian deskriptif. Metode ini dipilih oleh peneliti agar mendapatkan gambaran dari berbagai informasi aktual secara terperinci yang digambarkan pada aspek kemampuan keuangan daerah yang diukur melalui share PAD, growth PAD dan elasticity PAD yang kemudian dikombinasikan ke dalam metode indeks kemampuan keuangan daerah. Data yang dipilih merupakan data panel yang berupa Anggaran Pendapatan dan Belanja Daerah dari 9 Kabupaten/Kota yang masuk kategori daerah tertinggal selama rentang tahun 2015 – 2019 yang diperoleh dari Direktorat Jenderal Perimbangan Keuangan Kementerian Keuangan. Hasil yang diperoleh ada 6 Kabupaten yang masuk dalam klasifikasi kemampuan keuangan daerah tinggi, 2 Kabupaten masuk kedalam klasifikasi sedang dan 1 Kabupaten masuk dalam klasifikasi rendah. Kata kunci: Daerah Tertinggal, Growth PAD, Elasticity PAD, Indeks Kemampuan Keuangan Daerah, Share PAD